Studi Literatur Mengenai Pengaruh Literasi Pajak Terhadap Kepatuhan Wajib Pajak Di DKI Jakarta - Astati, Selfea Dewi; Dewi, Aisfitria Riski Dewi Riski; Firdaus, Muhammad Fahrizal; khoiriawati, Novi (Politeknik Sawunggalih Aji, 2025)
The impact of tax knowledge on taxpayer compliance in DKI Jakarta is examined in this study. In order to boost state revenue, taxpayer compliance is crucial. Nonetheless, the degree of compliance remains low in the DKI Jakarta area, presumably due to a lack of awareness regarding taxes. The Systematic Literature Review (SLR) type of qualitative research methodology is employed. The information is derived from ten pertinent articles. The results of the study show that taxpayer compliance rates are significantly improved by tax literacy. As seen by the recent decline in local tax revenue realization, taxpayers with high tax literacy are often more compliant, whereas those with low tax literacy are less compliant. This study also found that digital tax literacy is an important factor in the context of tax administration modernization, which is increasingly relevant in the current digital era; additionally, improving tax literacy can help reduce reporting errors and enhance transparency in tax management; and finally, the study's conclusion highlights the need to improve tax literacy through effective educational programs to encourage taxpayer compliance in Jakarta, thereby contributing to increased local tax revenue. Taxpayers with high tax literacy tend to better understand their rights and obligations, which leads to greater compliance in fulfilling their tax obligations.